2017
DOI: 10.5152/ced.2016.2293
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Infections in Newborn

Abstract: Sistemik fungal enfeksiyonlar yenidoğan bebeklerde, özellikle aşırı düşük doğum ağırlıklı prematürelerde yüksek mortalite ve morbidite oranlarına sahiptir. Prematüre bebekler, uzun süre parenteral beslenme, çoklu antibiyotik tedavileri, prematüriteden kaynaklanan bağışıklık yetmezliği nedeniyle fungal enfeksiyonlar için risk altındadırlar. Teknolojik gelişimle prematüre bebeklerin yaşam sınırının daha düşük gestasyon haftalarına çekilmesi sonucunda, yenidoğan yoğun bakım ünitelerinde invaziv girişimlerin, sant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Candida infections are the most common fungal infections in the neonatal period, especially in very low birth weight infants, with high morbidity and mortality rates. [ 8 ] It has been reported that Candida infections are responsible for 1.4% of the early neonatal sepsis and 2.6%–16.7% of late-onset sepsis in very low birth weight infants. [ 8 ] In a study examining single-center nosocomial infections, they found 61.9% Gram-positive bacteria, 30.9% Gram-negative bacteria, and 7.2% fungi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candida infections are the most common fungal infections in the neonatal period, especially in very low birth weight infants, with high morbidity and mortality rates. [ 8 ] It has been reported that Candida infections are responsible for 1.4% of the early neonatal sepsis and 2.6%–16.7% of late-onset sepsis in very low birth weight infants. [ 8 ] In a study examining single-center nosocomial infections, they found 61.9% Gram-positive bacteria, 30.9% Gram-negative bacteria, and 7.2% fungi.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] It has been reported that Candida infections are responsible for 1.4% of the early neonatal sepsis and 2.6%–16.7% of late-onset sepsis in very low birth weight infants. [ 8 ] In a study examining single-center nosocomial infections, they found 61.9% Gram-positive bacteria, 30.9% Gram-negative bacteria, and 7.2% fungi. [ 9 ] This rate has been reported to vary between 1.1% and 1.3% in studies in Europe [ 1 ] , and 4–7.7% in Asia.…”
Section: Discussionmentioning
confidence: 99%